En-face widefield optical coherence tomography angiography for understanding vascular networks changes in two cases of acute retinal necrosis - Mami Tomita; Mizuki Tagami; Norihiko Misawa; Atsushi Sakai; Yusuke Haruna; Shigeru Honda (Journal of Ophthalmic Inflammation and Infection, 2023)
Abstract Purpose The present study assesses the utility of en-face widefield optical coherence tomography angiography (OCTA) imaging for evaluating the retinal vascular network during the course of treatment in acute retinal necrosis(ARN). Observations OCTA images of two cases of acute retinal necrosis were analyzed. Case 1 was a 15-year-old male with visual crowding in his right eye who had best-corrected visual acuity of 16/20 and intraocular pressure of 25 mmHg in his right eye on initial evaluation. Case 2 was a 57-year-old male with visual crowding in his left eye who had best-corrected visual acuity of 20/20 in his left eye on initial examination and intraocular pressure of 19.3 mmHg. In both patients, dynamic changes could be tracked by en-face ultra-widefield OCTA imaging before and up to 1 year after surgical treatment. The images showed arteriovenous anastomosis and the nonperfused area on the surface of the retina. Conclusions and importance En-face widefield OCTA is useful for monitoring the structure of retinal vessels over time in acute retinal necrosis. Wide-angle OCTA is used to non-invasively examine retinal vascular dynamic changes in ARN. OCTA artifacts due to intraocular inflammation appeared, making interpretation difficult. These will remain as issues in the future. It seems difficult for a while to completely replace FA due to the problem of image clarity.